Pengaruh Faktor Geografis dalam Preferensi Pemilih Muda pada Pemilihan Presiden 2024 - Agung Satriyo Nugroho; Ramadhan, Kunastya Mulya Pinta; Pasaribu, Destriana (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
The dynamics of the 2024 general election, especially the presidential election, have begun in 2023. Data from the General Election Commission (KPU) states that of the 205 million Permanent Voter List (DPT), 52% are young voters aged 17-40 years. This is the basis importance of understanding the characteristics of young voters' preferences, especially when associated with geographical factors. This study aims to (1) map spatial distribution patterns and characteristics of young voters based on geographical factors; and (2) identify the influence of geographical factors in determining the preferences of young voters in the 2024 presidential election. Data were collected in a simple random sampling amounting to 425 samples with regional distribution throughout Indonesia. This research was carried out with a quantitative method based on statistical testing from the data collection process to data analysis and interpretation. Statistical testing used a comparative model test (kruskal-wallis/h-test), correlations (spearman rank), and regression. The result of this study showed that there are no significant differences between young voters who live in rural, urban, or residential areas based on regionalization.